Adhesion of Pollen Particles to Daily Disposable Soft Contact Lenses - Mimura, Tatsuya (Clin Optom (Auckl), 2021)
PURPOSE: Pollen and proteins attached to soft contact lenses (SCLs) exacerbate allergic conjunctivitis. The material of SCLs may affect the pollen adhesion to the SCLs. The factors associated with the number of pollen particles that are adherent to daily disposable SCL were investigated. METHODS: Pollen particles were experimentally exposed to the contact lens surface of 12 types of SCLs for 1 hour, and the SCLs were washed and rinsed with a physiological saline (n=10 for each SCL type). A total of 120 contact lenses were used in this study. The pollen particles attached to the SCL were observed and photographed under a microscope. The influence of the materials of the SCLs on the degree of pollen adhesion were investigated. RESULTS: The number of residual pollen particles attached to SCLs was in the range from 0–293/area of 200×200 µm. Percentage of pollen adhesion area of the surface of the SCL was in the range from 0.01% to 3.25%. There were significant differences in both the number and adhesion area of pollen particles among the 12 types of SCLs tested (P<0.0001 and P<0.0001, respectively). The number of pollen particles adhered to SCLs was significantly higher in colored SCLs than clear SCLs (unpaired t-test, p<0.001). The portion of pollen adhesion area was the lowest in the silicone hydrogel SCLs made with delefilcon-A (0.01 ± 0.02%). CONCLUSION: Pollen adhesion in daily disposable SCLs depends on the characteristics and materials of the SCLs and was high in colored SCLs and lowest in delefilcon-A silicone hydrogel SCL. These results suggest that colored SCLs are not preferred during pollen season.